Individual and cumulative health afflictions are associated with greater impairment in physical and mental function in former professional American style football players. Issue 1 (13th May 2021) - Tenforde, Adam S.; Cortez, Bryan; Coughlan‐Gifford, Elaine; Grashow, Rachel; Baker, Jillian; Baggish, Aaron L.; Pascual‐Leone, Alvaro; Nadler, Lee M.; Speizer, Frank E.; Taylor, Herman A.; Weisskopf, Marc G.; Zafonte, Ross
Abstract: Background: Former American style football players (ASF players) have recognized health concerns associated with prior sport participation. It remains unknown whether categorizations of current health conditions, referred to in this report as afflictions (conceptually framed as neurocognitive, cardiovascular, cardiometabolic, sleep apnea, and chronic pain) are associated with physical and mental function. Objective: To evaluate the association of afflictions to physical and mental function. It was hypothesized that former National Football League players with any affliction would have worse function compared to unafflicted participants. It was anticipated that multiple afflictions would result in cumulative loss of function. Design: Cross‐sectional retrospective design. Setting: Academic medical multisite hospital system. Participants: A total of 3913 of 15, 611 former ASF players who played professionally from 1960 to 2019 (response rate 25%). Assessment of Risk Factors : Self‐report survey. Main Outcome Measures: Each participant completed the Patient Reported Outcomes Measurement Information System (PROMIS) Global Health Scale and Physical Function questionnaires. Responses were used to generate two physical function and one mental function subscale scores. Raw scores were converted to T‐scores categorized as impaired (T‐score < 40) or unimpaired (T‐score ≥ 40). Primary analyses measured the association of affliction to function (impaired or unimpaired). Results: After adjusting for confounders (age, race, position, number of seasons, age of first exposure to football, alcohol use, smoking history, and current body mass index), each affliction was associated with reduced physical function on the Global physical function subscale (risk ratio [RR] = 1.23‐2.45, all P < .005), physical function scale (RR = 1.24‐2.75, all P < .01), and mental function scale (RR = 1.34‐2.87, all P < .001), except that cardiovascular affliction was not associated with mental function (RR = 1.15, P = .15). The lowest functional measures were observed in those afflicted by chronic pain. Cumulative afflictions were associated with worse function. Conclusions: Afflictions are associated with cumulative reduction of function. Research evaluating how afflictions interact may help elucidate mechanisms for illness and develop interventions to optimize function.